Algorithmic Cultural Mediation: TikTok as a Venue for Youth Identity Negotiation and Local Heritage Preservation in Southeast Asia - Dani Manesah (MD Research Center, 2025)
This study explores the role of TikTok as a medium for cultural expression and self-identity among teenagers in Southeast Asia, as well as its contribution to the preservation of local culture amid globalization. Using a qualitative approach, this research analyzes how TikTok enables young people to express their local culture, engage within global communities, and develop both personal and collective identities. Data were collected through literature review and content analysis of TikTok videos produced by users from various Southeast Asian countries. The main findings indicate that TikTok functions as a platform that democratizes cultural expression, allowing users to widely showcase traditional practices and socio-political issues. The platform also plays a role in social activism, with young users leveraging TikTok to raise awareness on issues like human rights and climate change. However, challenges arise related to cultural homogenization due to the dominance of global trends. This study concludes that TikTok can strengthen local cultural preservation while simultaneously providing space for global cultural exchange. Implications of this research highlight the importance of balancing participation in global culture with the preservation of local values, which can be optimized through cross-cultural collaboration. Further research is needed to explore the long-term impact of TikTok on the cultural and social identities of Southeast Asian youth.